Extracción del aceite esencial de sunfo (Clinopodium nubigenum Kunth Kuntze) por el método de arrastre de vapor, para su caracterización química, antioxidante y microbiológica. - Mena Ayala, Gabriela Katherine (2022)
The present work was carried out with the objective of characterizing sunfo essential oil (Clinopodium nubigenum Kunth Kuntze), and essential yield oil; Using Expert Design 8.0.6 software (Stad-Ease Inc., Minneapolis, USA), a mathematical model was established of surface response, where 17 experimental runs were obtained with operating variables of time (60, 105 and 150 min) and plant material/distilled water ratio (1:3, 1:4, 1:5). The process temperature was kept constant in function of water boiling, the essential oil was separated with a Clevenger trap equipment, then it was left to stand with 2 g of Na2SO4 for thirty minutes, and later the sample was decanted and filtered, subsequently It was packed in amber glass bottles. The best conditions of essential oil extraction were at a time of 150 min and a vegetable/distilled water ratio of 1:5, where an experimental yield was obtained of 1.5291%. In gas chromatography with mass detector, 23 compounds were found being pulegone (44.31%), menthone (22.05%) and thymol (14.39%) the main components. At antioxidant capacity were obtained 190.54 µmol Fe2+/g in FRAP and 289.84 µmol ET /g ABTS. The antimicrobial capacity was made through minimum inhibitory concentration where the essential oil showed effectiveness against Escherichia coli ATCC 25922, Pseudomonas aeruginosa ATTC 39327, Staphylococcus aureus ATCC 25923, Salmonella enterica.